2018
DOI: 10.3126/jnhrc.v16i3.21424
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug Use Pattern Using WHO Prescribing Indicators

Abstract: Background: In order to promote rational drug use in developing countries, assessment of drug use pattern using the World Health Organization drug use indicators is important. The aim of this study was to assess the drug prescription patterns at Kathmandu Medical College Teaching Hospital, using some of the World Health Organization core drug use indicators.Methods: A prospective cross-sectional study was carried out in order to determine current prescribing trends at Kathmandu Medical College Teaching Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
2
7
2
Order By: Relevance
“…The majority (94.59) of the drugs were prescribed by generic name, and the rest were prescribed by their brand names which was not in line with WHO guidelines recommendation of 100% generic prescription. The proportion of generic prescription was lower compared with findings by [31] results of a study in Saudi Arabia (38.06%) [5].…”
Section: Discussioncontrasting
confidence: 69%
“…The majority (94.59) of the drugs were prescribed by generic name, and the rest were prescribed by their brand names which was not in line with WHO guidelines recommendation of 100% generic prescription. The proportion of generic prescription was lower compared with findings by [31] results of a study in Saudi Arabia (38.06%) [5].…”
Section: Discussioncontrasting
confidence: 69%
“…Minimizing the use of injections not only reduces the cost of therapy but also lower the risk of complications related to parenteral use (19). In contrast to the results of other studies from Nepal (71%), Yemen (46%) and West Ethiopia (28.3%), we found low percentages of injection use in the present study (5.1%), (16,27,28).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Traincontrasting
confidence: 91%
“…Similarly, studies from Northwestern Ethiopia and India reported values within the acceptable range of 1.72 and 1.8, respectively (14,15). Several studies from different countries reported average number of drugs per encounter values higher than our results and WHO standards ranging from 2.2 to 5.85 (4,5,(16)(17)(18)(19)(20).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Trainsupporting
confidence: 71%
See 1 more Smart Citation
“…A study conducted in Nepal Katamandu medical college teaching hospital showed poly pharmacy (Average no. of prescription per encounter was 5.8 )and commonly used brand names for prescribing of the drugs 6 This study assessed the drug prescribing pattern in outpatient pharmacy of Jigjiga University, Sheikh Sultan Hassan Yabere Referral Hospital by using WHO prescribing indicator use.…”
Section: Introductionmentioning
confidence: 99%